Endaural Approach of External Auditory Canal Osteoma: Report of Two Cases / Che Mohd Hilmi Che Mat ...[et al.] - Che Mat, Che Mohd Hilmi; Salahuddin, Zulkiflee; Muhamed, Nik Azrizie; Mohamad, Irfan (Universiti Teknologi MARA Cawangan Selangor, 2021)
Osteomas occur in all parts of the temporal bone, including the mastoid, squamous, middle ear, styloid process, internal auditory canal and external auditory canal (EAC). The EAC has been reported to be the most common site, followed by the mastoid and squamous parts. Diagnosis is made based on history, clinical examination and radiological findings. Computed tomography reveals a pedunculated hyperdense mass that usually arises from the tympanosquamous suture. Surgical removal of EAC osteomas can be achieved using the endaural or postauricular approaches. It can be performed with a drill or osteotome, either endoscopically or by using microscopy. This report presents two patients with EAC osteomas who underwent excision under microscopy using the endaural approach. Surgery is the gold standard treatment, while close observation may be considered in asymptomatic patients.